2022
DOI: 10.1002/da.23277
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of early‐life unpredictability to neuropsychiatric symptom patterns in adulthood

Abstract: Background: Recent studies in both human and experimental animals have identified fragmented and unpredictable parental and environmental signals as a novel source of early-life adversity. Early-life unpredictability may be a fundamental developmental factor that impacts brain development, including reward and emotional memory circuits, affecting the risk for psychopathology later in life. Here, we tested the hypothesis that self-reported early-life unpredictability is associated with psychiatric symptoms in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The subsequent QUIC Spanish language validation study then also associated unpredictability assessed via the QUIC-SP to anxiety and depressive symptoms in adulthood (as well as anhedonia and poorer physical health; Liu et al, under review ). Building upon these findings, the QUIC has now also been linked to posttraumatic stress, anhedonic, depressive and anxiety symptoms as well as suicidal ideation in trauma-exposed male veterans ( Spadoni et al, 2022 ). Further, Gillespie and Rao (2022) recently documented associations between increased childhood unpredictability assessed with the QUIC with higher rates of depressive symptoms and compromised executive function in adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…The subsequent QUIC Spanish language validation study then also associated unpredictability assessed via the QUIC-SP to anxiety and depressive symptoms in adulthood (as well as anhedonia and poorer physical health; Liu et al, under review ). Building upon these findings, the QUIC has now also been linked to posttraumatic stress, anhedonic, depressive and anxiety symptoms as well as suicidal ideation in trauma-exposed male veterans ( Spadoni et al, 2022 ). Further, Gillespie and Rao (2022) recently documented associations between increased childhood unpredictability assessed with the QUIC with higher rates of depressive symptoms and compromised executive function in adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…MS has been described as an environment of deprivation and, to a lesser extent, threat (McLaughlin et al, 2014 ), and we have recently reported that MS confers an unpredictable environment as well (manuscript under review). Adversity within the dimensions of threat and unpredictability has particularly been associated with anxiety-like behaviors due to functional and developmental impairments of connectivity between regions such as the BLA, BNST, and prefrontal cortex (PFC; Tottenham et al, 2010 ; Hein and Monk, 2017 ; Spadoni et al, 2022 ). With a developmental study in males and females, we have observed that MS yields hyperinnervation from the basolateral amygdala to the prefrontal cortex, with females, in particular, displaying this hyperinnervation earlier in development (as early as P25), along with disrupted maturation of BLA-medial PFC functional connectivity (Honeycutt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research done in animals has illustrated that offspring exposed to unpredictable caregiver signals show a reduction in motivation and the experience of pleasure, characteristics of the trans-diagnostic symptom, anhedonia (Bolton et al, 2018). Work in humans accords with these findings, showing the relationships between experiences of ELU, reduced reward anticipation, and symptom severity in anhedonia, depression, and anxiety (Dillon et al, 2009;Goff et al, 2013;Hanson et al, 2016;Mehta et al, 2010;Spadoni et al, 2022).…”
Section: Introductionmentioning
confidence: 94%